THE EDUCATION-HEALTH GRADIENT - Conti, Gabriella (2010)
In this paper, we determine the role played by early cognitive, noncognitive, and health endowments. We identify the causal effect of education on health and health-related behaviors. We develop an empirical model of schooling choice and post-schooling outcomes, where both schooling and the outcomes determined in part by schooling are influenced by measured early family environments and latent capabilities (cognitive, noncognitive and health). We show that family background characteristics, and cognitive, noncognitive, and health endowments developed by age 10, are important determinants of labor market and health disparities at age 30. Not properly accounting for personality traits overestimates the importance of cognitive ability in determining adult health. Selection on factors determined early in life explains more than half of the observed difference by education in poor health, depression, and obesity. Education has an important causal effect in explaining differences in many adult outcomes and healthy behaviors. We uncover significant gender differences. We go beyond the current literature which typically estimates mean effects to compute distributions of treatment effects. We show how the health returns to education can vary among individuals who are similar with respect to their observed characteristics, and how a mean effect can hide gains and losses for different individuals. Our research highlights the important role played by the early years in producing health.